On the decomposition of a perturbed operator of weighted shift - Baskakov, A. G.; Баскаков, А. Г.; Баскаков, А. Г. (Institute of Mathematics, NAS of Ukraine, 1998)
We obtain results concerning the reducibility of an operator of weighted shift to a system of scalar operators of weighted shift.